PROBLEMS OF UZBEK LEARNERS WITH USING SUBORDINATING CONJUNCTIONS WHILE MAKING COMPLEX SENTENCES IN ENGLISH LANGUAGE - Turakulova, Dilafruz Muxammadsoli qizi (Educational Research in Universal Sciences, 2022)
This article covers problematic areas of using and learning subordinating conjunctions for Uzbek learners while making complex sentences in English language and presents possible solutions.